The social role of counseling in reducing the phenomenon of child labor Afield study in Lattakia province - Sadek, Husain; AL-Baerk, Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Someone accelerates Bmendilh vial of water into your car, take the second table (juices and gases) to replace his trade, and the third stands on the edge of the main road to sell you perfume sometimes and at other times a little game ... their bodies show the features of poverty and destitution. This is what you see our eyes and perhaps what cryptic greatest When poverty rise in capacity and depth and fairness are the inevitable social virtually absolute, a child will be forced to work to help the family to live and this work will inevitably be subject to parting with the school from the entrance of priorities, here are a global show poverty is a global level this phenomenon (child labor), which causes and manifestations do not differ in many communities, and the effects do not stop at the borders of hunger and disease rather than to the philosophical debate exists is: (to be or not to be); as one finds of these same children have to manage profiteers his day in order to live and for this you see looking for the establishment of balances allow him to ease the pressure on him through the use of drugs, has required him to enter the violence and criminality factor. Through the pages of this search a number of objectives which will identify the causes of child labor and economic and social conditions and to identify the environment and social and economic conditions of their families and their relationship with each other and the relationship with the employer and the outlook for them.